Calibrating the 'right values': the role of critical inquiry tasks in social studies textbooks. (February 2019) - Myskow, Gordon
The issue of how to represent a nation's past in history textbooks has been the source of vigorous debate across a variety of educational contexts. Some textbooks have been criticized for their simplistic, nation-building stories and the meta-narrative of 'progress' they engender. While many contemporary textbooks include critical inquiry tasks for developing learners' historical thinking skills, the extent to which they actually facilitate critical thinking is unclear. This article employs methods grounded in Systemic Functional Linguistics (SFL) for analyzing verbal and visual text to examine evaluative meaning in the core narrative and two critical inquiry tasks of a Canadian social studies textbook chapter. The findings show an uneasy coexistence between the aims of providing opportunities for critical engagement and communicating a cohesive story of the nation's collective experiences. Rather than platforms for facilitating interpretive independence, the critical inquiry tasks appear to be spaces for drawing out or calibrating the 'right values' developed through the core narrative of the chapter.